NR2F1 regulates regional progenitor dynamics in the mouse neocortex and cortical gyrification in BBSOAS patients. (2nd June 2020) - Bertacchi, Michele; Romano, Anna Lisa; Loubat, Agnès; Tran Mau‐Them, Frederic; Willems, Marjolaine; Faivre, Laurence; Khau van Kien, Philippe; Perrin, Laurence; Devillard, Françoise; Sorlin, Arthur; Kuentz, Paul; Philippe, Christophe; et al.
Abstract: The relationships between impaired cortical development and consequent malformations in neurodevelopmental disorders, as well as the genes implicated in these processes, are not fully elucidated to date. In this study, we report six novel cases of patients affected by BBSOAS (Boonstra‐Bosch‐Schaff optic atrophy syndrome), a newly emerging rare neurodevelopmental disorder, caused by loss‐of‐function mutations of the transcriptional regulator NR2F1 . Young patients with NR2F1 haploinsufficiency display mild to moderate intellectual disability and show reproducible polymicrogyria‐like brain malformations in the parietal and occipital cortex. Using a recently established BBSOAS mouse model, we found that Nr2f1 regionally controls long‐term self‐renewal of neural progenitor cells via modulation of cell cycle genes and key cortical development master genes, such as Pax6 . In the human fetal cortex, distinct NR2F1 expression levels encompass gyri and sulci and correlate with local degrees of neurogenic activity. In addition, reduced NR2F1 levels in cerebral organoids affect neurogenesis and PAX6 expression. We propose NR2F1 as an area‐specific regulator of mouse and human brain morphology and a novel causative gene of abnormal gyrification. Synopsis: This study reveals brain cortical folding defects, linked to intellectual disability, in patients with BBSOA syndrome, a rare genetic disorder caused by haploinsufficiency of the transcription factor NR2F1. In mice, Nr2f1 exerts regional control of neural progenitor (NP) self‐renewal and differentiation. Human NR2F1 is expressed in a gradient along primary neocortical convolutions. BBSOAS patients display previously unreported neocortical malformations, such as polymicrogyria‐like aberrant folding and expanded occipital convolutions. Nr2f1 heterozygous and homozygous mutant mice partially recapitulate the human disease and display neocortical malformations. Nr2f1 orchestrates NP proliferation and differentiation by acting as a pro‐neurogenic factor. Nr2f1 modulates NP cell cycle dynamics by regulating P21 and Pax6 expression. Abstract : Reduced levels of the neuronal differentiation factor NR2F1/COUP‐TFI impairs brain cortex folding in humans, and disrupts regional neural progenitor dynamics in the neocortex of a BBSOAS disease mouse model.